2004
DOI: 10.1007/s11176-005-0066-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and physicochemical properties of girded porphyrins

Abstract: b-Alkyl-substituted 5,15-diphenylporphyrins are synthesized, whose phenyl rings are connected through the ortho positions by bridging groups of various length. The resulting porphyrins were characterized by the electronic absorption and 1 H NMR spectra, and their structure was calculated by the molecular mechanics method. The kinetics of complex formation of the synthesized porphyrins with copper(II) acetate in acetic acid and pyridine depend on the degree of shielding of the reaction center in the tetrapyrrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The mass spectrum (electron impact, 70 eV) was obtained on an MKh-1310 instrument (ion source temperature 150-200°C). 2,2′-Methylenebis(3-ethyl-4-methyl-1H-pyrrole) (IV) was synthesized according to the procedure described in [12,13]; 3,4-dimethyl-1H-pyrrole-2-carbaldehyde (V) was prepared as reported in [14]. Organic solvents were purified by known methods [15].…”
Section: Methodsmentioning
confidence: 99%
“…The mass spectrum (electron impact, 70 eV) was obtained on an MKh-1310 instrument (ion source temperature 150-200°C). 2,2′-Methylenebis(3-ethyl-4-methyl-1H-pyrrole) (IV) was synthesized according to the procedure described in [12,13]; 3,4-dimethyl-1H-pyrrole-2-carbaldehyde (V) was prepared as reported in [14]. Organic solvents were purified by known methods [15].…”
Section: Methodsmentioning
confidence: 99%
“…The rate constant of dissociation of the copper complex with the central tetrapyrrole fragment was determined using the same method as described above for the complex formation. The transformation of Cu 3 TP into (H 4 P 2+ ) 3 did not result in the change of absorbance of the solution at the stage of the Cu 2 H 2 TP complex dissociation (Fig. 2); hence, the absorbance change at that wavelength reflected the stability of the copper(II) complex with the central tetrapyrrole ring.…”
mentioning
confidence: 94%
“…The earlier studies on formation and dissociation of metal complexes with mono-and dimeric porphyrins in organic solvents [1][2][3][4][5][6] have revealed that distortion of the porphyrin fragments planarity significantly affects the reactions kinetics. In extension of our studies of spatially distorted porphyrins, we have prepared the trimeric porphyrin-type ligand H 6 TP and the corresponding binuclear Сu 2 Н 2 ТР (see Scheme 1) and trinuclear Сu 3 ТР copper complexes [7].…”
mentioning
confidence: 99%